Praesentia carnalis Christi. Incarnation Terminology in the Anti-heretical Polemic of Philastrius of Brescia - Szram, Mariusz (Vox Patrum, 2023)
The terminology found in one of the oldest Latin catalogs of heresies, Diversarum hereseon liber, written by Philastrius, bishop of Brescia (330-387/388), was adapted to the needs of anti-heretical polemics, and at the same time reflected the way of talking about Christ’s earthly mission, characteristic of the Latin patristic literature of the second half of the 4th century. A detailed philological and theological analysis of Philastrius’s treatise led to the following conclusions: (1) The terminology used by the author was rooted in the early Christian tradition (caro, corpus, incarnatio, incorporatio), but also original through the use of his own formula praesentia carnalis; (2) The vocabulary used in the catalog was strictly dependent on the subject of the doctrinal dispute. In polemics with docetistic heresies, Philastrius used the term caro more often than corpus, describing the body and, indirectly, the entire human nature of Christ. In the discussion with heresies that did not directly address the subject of the body of Christ, and also when presenting the orthodox teaching of the Church on the Incarnation of the Son of God, he used the term incorporatio more often than incarnatio; (3) The favorite phrase used by the Bishop of Brescia to describe the Incarnation was praesentia carnalis Christi. With it, Philastrius emphasized several important aspects of the theology of the Incarnation: the real corporeality of the person of Christ; the presence of the Son of God among people and its salvific purpose; a long process of revealing God to man, related to the Old Testament prophecies, the fulfillment of which was the coming of the Savior to earth.